1969
DOI: 10.1085/jgp.54.6.713
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Active Transport of Calcium in Human Red Cells

Abstract: The Ca ++ transport mechanism in the red cell membrane was studied in resealed ghost cells. It was found that the red cell membrane can transport Ca ++ from inside the cell into the medium against great concentration gradient ratios. Tracing the movement of 45Ca infused inside red cells indicated that over 95 % of all Ca ++ in the cells was transported into media in 20 min incubation under the opdmum experimental conditions. The influence of temperature on the rate constant of transport indicated an activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…Previously, it was found that when red blood cells are fragmented, red blood cell membrane fragments (RBCMF) were found to take up Ca ++ and this Ca ++ uptake is accompanied by ATP hydrolysis by Mg++-activated ATPase (Lee and Shin, 1969;Cha et al 1971). It has been suggested that this Ca ++ uptake is due to the presence of inside out vesicles in the present system although not all of the vesicles are inside out (Steck et al, 1970;Weiner and Lee, 1972).…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previously, it was found that when red blood cells are fragmented, red blood cell membrane fragments (RBCMF) were found to take up Ca ++ and this Ca ++ uptake is accompanied by ATP hydrolysis by Mg++-activated ATPase (Lee and Shin, 1969;Cha et al 1971). It has been suggested that this Ca ++ uptake is due to the presence of inside out vesicles in the present system although not all of the vesicles are inside out (Steck et al, 1970;Weiner and Lee, 1972).…”
Section: Introductionmentioning
confidence: 74%
“…It has been established that Na+-K+-activated ATPase and Ca++-activated ATPase are intimately associated with outward extrusion of Na + and Ca 2+, respectively (Skou, 1957 and1965;Hoffman, 1961;Schatzmann, 1966;Albers, 1967;Post et al, 1969;Schatzmann and Vincenzi, 1969;Lee and Shin, 1969). Since the present RBCMF has both of the above two ATPase activities, an attempt has been made to investigate the similarity of these two active transport systems in molecular mechanisms.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been previously shown that the red cell membrane has an active Ca++ extrusion mechanism (Schatzmann, 1966;Schatzmann and Vincenzi, 1969;Lee and Shin, 1969). Also, it was found that the fragmented red cell membrane splits ATP in the presence of Mg + + and this Mg++ ATPase activity is greatly stimulated by Ca + + .…”
Section: Introductionmentioning
confidence: 96%